2011
DOI: 10.1523/jneurosci.2194-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Tonic Dopamine Induces Persistent Changes in the Transient Potassium Current through Translational Regulation

Abstract: Neuromodulatory effects can vary with their mode of transmission. Phasic release produces local and transient increases in dopamine (DA) up to micromolar concentrations. Additionally, since DA is released from open synapses and reuptake mechanisms are not nearby, tonic nanomolar DA exists in the extracellular space. Do phasic and tonic transmissions similarly regulate voltage dependent ionic conductances in a given neuron? It was previously shown that DA could immediately alter the transient potassium current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 75 publications
(125 reference statements)
1
43
0
Order By: Relevance
“…Experimental and computational studies suggest that distinct conductance ratios are maintained in identified pyloric neurons, including the ratio of LP I A to I h (Schulz et al, 2006(Schulz et al, , 2007Hudson and Prinz, 2010), and modulators are necessary for their maintenance (Khorkova and Golowasch, 2007). Interestingly, steadystate DA also regulates LP I A G max (Rodgers et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Experimental and computational studies suggest that distinct conductance ratios are maintained in identified pyloric neurons, including the ratio of LP I A to I h (Schulz et al, 2006(Schulz et al, , 2007Hudson and Prinz, 2010), and modulators are necessary for their maintenance (Khorkova and Golowasch, 2007). Interestingly, steadystate DA also regulates LP I A G max (Rodgers et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…By convention the first spike in the pyloric dilator neuron (PD) defines the beginning of a pyloric cycle, and the phasing of pyloric neurons is determined relative to the start of the cycle. Since we were interested in recovery mechanisms intrinsic to LP, we broke with convention and used the last spike in PD to define the beginning of the cycle, because tonic DA can cause persistent changes in PD ionic conductances (Rodgers et al, 2011). One cycle period was therefore defined as the last spike in one PD burst to the last spike in the next PD burst (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…cAMP/protein kinase A signaling has been found to be important for DA to modulate I A in LP neurons (Zhang et al, 2010). Additionally, this K current has been shown to be enhanced by tonic stimulation with nanomolar DA concentration through a translationdependent mechanism involving the target of rapamycin pathway in crustacean LP neurons (Rodgers et al, 2011), a process thought to dampen extrinsic excitatory inputs.…”
Section: Ion Channels Modulated By Damentioning
confidence: 99%